Aggressive Adenomatoid Odontogenic Tumor of Maxilla involving Impacted Third Molar: A Rare Case Report - Subrat Kumar Padhiary; Gunjan Srivastava; Satyabrat Patnaik MDS; Neeta Mohanty; Sourav Chandra B Bal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Adenomatoid odontogenic tumor (AOT) is a rare tumor comprising about 2.2% to 7.1% of all odontogenictumors. It is a neoplasm of odontogenic origin having slow-growth rate, noninvasive and benign in nature.Here, we report a case of a young female patient who presented with an aggressive AOT in maxilla involvingthe impacted third molar. Usually, the treatment for AOT comprises of enucleation and curettage, whereasdue to the fast growth rate and aggressiveness of the lesion, subtotal maxillectomy was performed in thiscase. The authors have described about the clinical, radiographic, histopathological and surgical aspect ofthe case.